2006
DOI: 10.1080/01443610600797426
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of and factors associated with meconium staining of the amniotic fluid in a Nigerian University Teaching Hospital

Abstract: This study was conducted to determine the incidence of meconium staining of the amniotic fluid (MSAF) and its associated factors in a Nigerian teaching hospital. Perinatal data on 80 consecutive live, singleton infants of booked mothers born through meconium-stained liquor from March - June 2003 were analysed and compared with babies born through clear liquor. The incidence of MSAF was 20.4% for 393 deliveries. The rate increased with gestational age: no case was found below 37 weeks (p = 0.001). Primiparity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
20
4
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 9 publications
18
20
4
1
Order By: Relevance
“…17 David et al in their study reported that 48% were male and 52% female and was contradictory to the present study. 19 Eva Guachan et al in their study had M:F ratio of 1.8:1 which was in line with our study. 20 In a developing country like ours, such a vast difference based on sex can be attributed to the uneven male female ratio and it is historically proven that MSAF was more common in male babies.…”
supporting
confidence: 81%
“…17 David et al in their study reported that 48% were male and 52% female and was contradictory to the present study. 19 Eva Guachan et al in their study had M:F ratio of 1.8:1 which was in line with our study. 20 In a developing country like ours, such a vast difference based on sex can be attributed to the uneven male female ratio and it is historically proven that MSAF was more common in male babies.…”
supporting
confidence: 81%
“…8,9 In the studies done in India, the range of incidence varied from 7.4% to 14.3%. [10][11][12] In the present study, the incidence was 27% which is higher than reported in most of the literature.…”
Section: Discussioncontrasting
confidence: 54%
“…David et al found that fetal heart rate abnormality and low apgar was seen in MSAF group. 12 In spite of debate, there are still a number of unresolved controversies concerning management of the labour with meconium stained amniotic fluid. Nevertheless most obstetricians feel unsafe about the state of the fetus if meconium stained liquor is seen.…”
Section: Discussionmentioning
confidence: 99%
“…Although the precise etiology of MSAF is still unclear, risk factors for MSAF include advanced gestational age at delivery, mode of delivery, increased duration of rupture of membranes (ROM), prolonged second stage of labor, and intra-amniotic infection [8,9,15,17,20,21]. Recently, Cheng et al [20] demonstrated that the longer the duration of the second stage of labor, the higher the frequency of MSAF (21% when the second stage was less than 1 h, and 28% when it was longer than 3 h).…”
Section: Introductionmentioning
confidence: 99%